I know that $$ \int_{0}^{+ \infty} e^{- x^{2}} dx = \frac{\sqrt{\pi}}{2}. $$

My question is: $$ \int_{0}^{1} e^{- x^{2}} dx = ~? $$

  • 4
    $\begingroup$ I think one can only do it numerically. $\endgroup$
    – user9464
    Sep 19, 2011 at 3:36
  • $\begingroup$ Well, there are ways to numerically compute the error function, much as you'll need a numerical method to compute $\sin\,1$... $\endgroup$ Sep 19, 2011 at 3:40
  • 1
    $\begingroup$ See here: en.wikipedia.org/wiki/Error_function for more information. $\endgroup$
    – Adam Saltz
    Sep 19, 2011 at 3:52

3 Answers 3


Since $$ e^{-x^2}=\sum_{k=0}^\infty\frac{(-x^2)^k}{k!} $$ we get by integrating that $$ \int_0^te^{-x^2}\,\mathrm{d}x=\sum_{k=0}^\infty(-1)^k\frac{t^{2k+1}}{(2k+1)k!} $$ Therefore, $$ \int_0^1e^{-x^2}\,\mathrm{d}x=\sum_{k=0}^\infty\frac{(-1)^k}{(2k+1)k!} $$ which converges pretty quickly.

Unilateral Power Series

A bit more complicated, yet yielding a non-alternating series, is to note that if we define $$ f(x)=e^{x^2}\int_0^xe^{-t^2}\,\mathrm{d}t $$ Then $f'(x)=1+2xf(x)$ and $$ f(x)=\sum_{k=0}^\infty a_kx^k $$ yields $2a_{k-1}=(k+1)a_{k+1}$. Using $f(0)=0$ and $f'(0)=1$ gives $a_{2k+1}=\dfrac{2^k}{(2k+1)!!}$. Thus, $$ \int_0^xe^{-t^2}\,\mathrm{d}t=e^{-x^2}\sum_{k=0}^\infty\frac{2^kx^{2k+1}}{(2k+1)!!} $$ Therefore, $$ \int_0^1e^{-t^2}\,\mathrm{d}t=e^{-1}\sum_{k=0}^\infty\frac{2^k}{(2k+1)!!} $$

  • $\begingroup$ Nice to see the double factorial popping up every so often... :) $\endgroup$ Jan 16, 2013 at 17:19

$\mathrm{erf}(z)$ is the "error function" encountered in integrating the normal distribution (which is a normalized form of the Gaussian function). It is an entire function defined by $$\mathrm{erf}(z)=\frac{2}{\sqrt{\pi}}\int_{0}^{z}e^{-t^2}\mathrm{dt}$$ Note that some authors (e.g., Whittaker and Watson 1990, p. 341) define $\mathrm{erf}(z)$ without the leading factor of $2/\sqrt{\pi}$.

Your question's solution is $$\int_{0}^{1}e^{-r^2}\mathrm{dr}=\frac{\sqrt{\pi}}{2}\mathrm{erf}(1)$$

You can get approximate value by using series $$\mathrm{erf}(x)=\frac{e^{-x^2}}{\sqrt{\pi}}\sum^{\infty}_{n=0}\frac{(2x)^{2n+1}}{(2n+1)!!}$$

Hope this helped.

Added. approximate value of $\mathrm{erf}(1)$ with 20 digits is


so the value is


  • 3
    $\begingroup$ You could also use the series $$ \int_0^x e^{-r^2}\ dr = \sum_{k=0}^\infty \frac{(-1)^k x^{2k+1}}{k!(2k+1)}$$ $\endgroup$ Sep 19, 2011 at 4:35
  • 3
    $\begingroup$ I prefer the series ks0830 used to the usual Maclaurin series; it's less prone to subtractive cancellation. $\endgroup$ Sep 19, 2011 at 15:21
  • $\begingroup$ When I have to eveluate an alternating series like this, I either separately accumulate the positive and negative terms or see if, for large enough $n$, $a_{2n}-a_{2n+1}$ has constant sign. $\endgroup$ Dec 23, 2012 at 22:13
  • 1
    $\begingroup$ @J.M.: I show these two methods and an asymptotic expansion here. $\endgroup$
    – robjohn
    Dec 24, 2012 at 9:57

According to Laplace, Legendre and the two masters of continued fractions, Jacobi and Ramanujan, $$ \int_{0}^{1} e^{- x^{2}} \,d{x} = \frac{\sqrt{\pi}}{2} - \cfrac{\frac{1}{2} e^{-1}}{1 + \cfrac{1}{2 + \cfrac{2}{1 + \cfrac{3}{2 + \cfrac{4}{1 + \cfrac{5}{2 + \cdots}}}}}}. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.